Analisis Faktor yang Mempengaruhi Keputusan Konsumen dalam Membeli Produk Pakaian Secara Online di Desa Air Lelangi Kecamatan Ulok Kupai Kabupaten Bengkulu Utara - Lian Sugiyarti; Sazili Sazili (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aimed to know the factors affecting consumer decision in buying clothing products online in Air Lelangi Village, Ulok Kupai District, North Bengkulu Regency.This study used descriptive method. The data sources of this study used primary data and secondary data. The data collection techniques of this study used observation, interview, documentation. This study used 3 data analysis techniques, namely data reduction data, data display, and conclusion. The results of the study show that there are some factors affecting consumer decision in buying clothing products online in Air Lelangi Village, Ulok Kupai District, North Bengkulu Regency.There are 3 indicators, namely 1) consumers choose products/services to meet their needs, when consumers make choices of diverse products/services, they do not regardless of the need to choose products, most consumers buy clothing products in online stores/marketplaces by considering the quality and effectiveness of the product. 2) Estimated time regarding the estimate of how long it take for the goods to be delivered to consumers, ranging from 3-7 days for delivery. 3) The need for products is also supported by the ease of choice of payment methods, consumers make choices about the method / method of payment for products to be purchased, consumers tend to use the COD method or pay on the spot.